The Every, or at last a sense of order, or the final days of free will, or limitless choice is killing the world - Eggers, Dave ([Circle, 2021)
"From the award-winning, bestselling author of The Circle comes an exciting new follow-up. When the world's largest search engine/social media company, The Circle, merges with the planet's dominant e-commerce site, it creates the richest and most dangerous--and, oddly enough, most beloved--monopoly ever known: The Every"--